Fish protein hydrolysate for fish health - Abdullah, Farah Izana; Hamid, Nur Hidayahanum; Abd Karim, Murni Marlina; Ismail, Mohd Fakhrulddin; Sin, Nur Leena Wong Wai; Kamaruddin, Mohd Salleh (Elsevier, 2024)
As a top global player in the aquaculture industry, Malaysia has the potential to commercially produce Fish Protein Hydrolysate (FPH) to fulfil global aquafeed demands. Considering a large amount of fish byproducts produced from the head, guts, viscera, the bones, fins, scales and skin, this byproducts can be turned into valuable resources. This review aims to critically analyze the source of a FPH in terms of the production process, factors affecting the quality of fish hydrolysate and the benefit to aquaculture. Both fish and fish byproducts can be used as a source for the manufacturing of FPH. The production of FPH consists of three major stages; Pre-treatment, Hydrolysis, and Recovery. Protein hydrolysis can be accomplished via biological or chemical techniques. Enzymatic hydrolysis was preferable to produce FPH in high value-added products. The recovery step mainly involves separation, concentration, and drying process. There are two ways to make FPH: liquid and dry. Dried FPH is preferred since it has a longer shelf life and is simpler to store and transport. The (had a significant impact on the FPH's solubility, emulsifying capabilities, foaming ability, fat absorption capacity, and bitterness. Moreover, FPH possessed anti-oxidative, anti-hypertensive, antibacterial, immunomodulatory, growth-like hormone and anti-stress peptides. The number of goblet cells and the size of the villi served as excellent measures of the health and condition of the fish intestinal mucosa. These results support the notion that dietary hydrolysate supplementation improves intestinal health and condition and has positive effects on the intestinal mucosa.